Alpha 1, 3-Galactosyltransferase Deficiency in Pigs Increases Sialyltransferase Activities That Potentially Raise Non-Gal Xenoantigenicity. (25th October 2011) - Park, Jong-Yi; Park, Mi-Ryung; Kwon, Deug-Nam; Kang, Min-Hui; Oh, Mihye; Han, Jae-Woong; Cho, Ssang-Goo; Park, Chankyu; Kim, Dong-Ku; Song, Hyuk; Oh, Jae-Wook; Kim, Jin-Hoi
Abstract : We examined whether deficiency of the GGTA1 gene in pigs altered the expression of several glycosyltransferase genes. Real-time RT-PCR and glycosyltransferase activity showed that 2 sialyltransferases [ α 2, 3-sialyltransferase ( α 2, 3ST) and α 2, 6-sialyltransferase ( α 2, 6ST)] in the heterozygote GalT KO liver have higher expression levels and activities compared to controls. Enzyme-linked lectin assays indicated that there were also more sialic acid-containing glycoconjugate epitopes in GalT KO livers than in controls. The elevated level of sialic-acid-containing glycoconjugate epitopes was due to the low level of α -Gal in heterozygote GalT KO livers. Furthermore, proteomics analysis showed that heterozygote GalT KO pigs had a higher expression of NAD + -isocitrate dehydrogenase (IDH), which is related to the CMP- N -acetylneuraminic acid hydroxylase (CMAH) enzyme reaction. These findings suggest the deficiency of GGTA1 gene in pigs results in increased production of N -glycolylneuraminic acid (Neu5Gc) due to an increase of α 2, 6-sialyltransferase and a CMAH cofactor, NAD + -IDH. This indicates that Neu5Gc may be a critical xenoantigen. The deletion of the CMAH gene in the GalT KO background is expected to further prolong xenograft survival.